2019
DOI: 10.3389/fmats.2019.00280
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Drawing of Commercial Poly(Lactic Acid) (PLA) Based Filaments

Abstract: In the present work, solid-state drawing of commercial PLA-based extruded filaments was investigated. Two different filaments were used: one based on neat PLA and the other based on PLA filled with copper particles. The effect of the processing parameters such as the drawing temperature and the draw ratio on the materials morphology and thermal and mechanical behavior was analyzed. A specially designed device which simulates the solid-stated drawing stage frequently used for fibers manufacturing was applied. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…The lowest draw ratio and the lowest temperature lead to the highest value for the elastic modulus, which could be attributed to the competition between the orientation of the macromolecular chains subjected to stretching and the relaxation of the same chains during stretching, which is hindered at a lower temperature [ 42 ]. Similar results were found by Walker et al for commercial PLA-based extruded filaments [ 43 ]. At the highest draw ratio, the decrease in stiffness, but also in the strain at break, could be associated with void generation due to overdrawing, but a deeper microstructural analysis is required to fully explain these findings [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…The lowest draw ratio and the lowest temperature lead to the highest value for the elastic modulus, which could be attributed to the competition between the orientation of the macromolecular chains subjected to stretching and the relaxation of the same chains during stretching, which is hindered at a lower temperature [ 42 ]. Similar results were found by Walker et al for commercial PLA-based extruded filaments [ 43 ]. At the highest draw ratio, the decrease in stiffness, but also in the strain at break, could be associated with void generation due to overdrawing, but a deeper microstructural analysis is required to fully explain these findings [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the Xc of the PFs and melt-electrospun fibers were very low (17.93% and 8.72%, respectively), whereas the Xc after fiber drawing was 58.83%. The absence of a glass transition in DSC thermograms often occurs when the crystalline fraction is more abundant than the amorphous fraction, and the Tcc value is absent because the DF is fully drawn, in agreement with previous studies [49]. The melt-electrospun fibers are, therefore, more similar to a PF than a DF.…”
Section: Physical Properties Of Pla Fibers Under Different Processingsupporting
confidence: 90%
“…Numerous processing methods have been developed to improve the strength of the polymers. Many studies have demonstrated that solid-state drawing (SSD) can induce self-reinforcement through the maximization of macromolecular chain orientation in polymeric materials [ 80 , 81 , 82 ]. Im et al (2016, 2017) determined that the tensile strengths of PLLA monofilaments and films could be increased up to two- and nine-fold, respectively, by increasing the draw ratio using a directly designed processing machine for the SSD method ( Figure 17 a) [ 83 , 84 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%